Effect of antiseptic solutions on wound healing: Integrative review (Research, Society and Development, 2024)
Introduction: The existence of a wound causes physical discomfort for a person, changes in this individual's life in all areas can be caused by the appearance of an injury, creating difficulties in accepting their self-image. Therefore, a very important moment when applying a dressing is the choice of products that will be used to clean the wound, as they directly influence the healing process of the injury. The application of substances in different situations seems to highlight the need to systematize the real technical-scientific understanding of the action of antiseptics, their indications and contraindications. Objective: To investigate the action of different antiseptic solutions on wound healing. Method: this is an integrative review, developed between August and October 2023. Results: 8 articles were analyzed, 1 study dealing with the action of sodium hypochlorite in chronic wounds, 2 addressing the action of chlorhexidine gluconate in concerns toxicity and implications in the healing process, 1 demonstrating the effect of chlorhexidine and povidone-iodine, 1 presenting the action of 70% ethanol, chlorhexidine gluconate, sodium hypochlorite, povidone-iodine and polyhexanide, 1 bringing implications of polyhexamethylene biguanide in healing and, for Finally, 2 studies reporting the action of povidone-iodine. Conclusion: The use of antiseptics on wounds demands technical-scientific knowledge. There is a greater number of experiments carried out in controlled environments, and in a way, it is important to further investigate the action of antiseptics on individuals who, in fact, have a wound.